Prognostic Factors of Biologic Therapy in Pediatric IBD - Anna Buczyńska; Urszula Grzybowska-Chlebowczyk (MDPI AG, 2022)
This was a retrospective cohort study aimed at identifying parameters measured at diagnosis of pediatric IBD to predict subsequent biologic therapy, as an equivalent to an unfavorable clinical course. Identification of predictors of poor outcomes is an important issue in current ECCO guidelines on pIBD. The study population consisted of 119 children with Crohn's disease and 112 with ulcerative colitis, diagnosed and monitored for at least 1 year from 2009-2019. The population was divided into the study groups separately: 39 children with CD and 14 with UC who received biologics before the age of 18 y compared to 80 with CD and 98 with UC who did not. The combined analysis of 53 biologic therapy recipients vs. 178 non-recipients with IBD was also conducted. Logistic regression tests (OR, RR) and sensitivity, specificity, PPV, and NPV were used. Factors significantly correlated with subsequent biologic therapy were perianal disease, complicated disease behavior, high PCDAI (CD), fatigue, hypoalbuminemia, high PUCAI (UC) and fever, fatigue, hypoalbuminemia, hypoproteinemia, and elevated CRP (IBD). Marginally significant factors were ileocecal disease, elevated serum IgA, anemia, and L4a-L4b coexistence. Apart from parameters already accepted as POPO (B2/3, perianal disease), interesting observations are the significance of IgA, L4a-L4b in CD, and hypoalbuminemia in UC.